Retrovesical cysts in boys-case series and literature review - Niklas Pakkasjärvi; Tiia Mönttinen; Lasse Hokkinen; Eija Mäkelä; Seppo Taskinen (SpringerOpen, 2022)
Abstract Background Retrovesical cysts present with varying etiologies. We initiated this study to provide insights into retrovesical cysts in boys through a case series and systematic literature review and to aid in treatment alternatives. Materials and methods Case series of seven patients from the in-hospital register with a systematic literature review on retrovesical cysts in children. Results We identified seven patients from the in-hospital register during 2005-2020 and eighty-two patients from the literature review. The literature review showed that children's retrovesical cysts are mainly asymptomatic before puberty. Those detected earlier in childhood present mostly with renal abnormalities. In our series, retrovesical cysts derived from three distinct etiologies with different treatment modalities. Asymptomatic cysts do not need excision and are to be followed up through puberty, but in the case of an ectopic ureter, nephroureterectomy is optional. Symptomatic retrovesical cysts may demand surgical excision. Ultrasonography is usually sufficient for diagnosis, but MRI provides better anatomical delineation and aids in surgical planning. Conclusions Retrovesical cysts in boys are benign conditions associated with abnormal development of the ureter and kidney. Ultrasonography is sufficient for diagnosis, with MRI giving further detail for surgical planning. Treatment consists of cyst excision, heminephrectomy/nephrectomy, transurethral canalization, or excision of prostatic utricle, depending on etiology. Asymptomatic cases are to be followed up through puberty, but in cases of an ectopic ureter, nephroureterectomy is preferred.